Evidence of Discrimination Against Afrocolombians in the Colombian Labor Market in Major Cities in 2007 (2015)
This paper evaluate the hypothesis that race is a determining factor in access to quality employment in Colombia during 2007 -- Using data from the Large Integrated Household Survey (2007-I), we estimate a generalized ordered logit model -- The results provide evidence that individuals self-identified as Afrocolombian have a higher probability of being in a low quality job than other Colombians -- This probability is higher by 1.9% in Cali, 3.4% in Bogotá, 12.6% in Barranquilla, 1.8% in Cartagena, 1.1% in Medellin and 3.8% overall in these five cities, results that could indicate that there is racial discrimination against Afrocolombians in the Colombian labor market